Immunisation with live attenuated Salmonella dublin expressing a sporozoite protein confers partial protection against Theileria parva - Heussler, V.T.; Taracha, E.L.N.; Musoke, A.J.; Duchateau, L.; McKeever, Declan J. (Elsevier, 1998)
Cattle immunised with a recombinant form of p67, the major surface antigen of Theilleria parva sporozoites, have been shown to be protected against parasite challenge. In an attempt to simplify the immunisation procedure live attenuated Salmonella strains expressing p67 have been constructed and used to induce anti-p67 immune responses in cattle. All animals immunised with these strains developed strong antibody responses to p67. Specific T cell responses could be detected in the majority of immunised cattle. Challenge with T. parva sporozoites revealed a significant level of protection in immunised calves compared to naive control animals or animals inoculated with non-recombinant attenuated Salmonella.